Three Essays on the Macroeconomic Impact of Inflation Targeting - Khan, Najib (Université d'Ottawa / University of Ottawa, 2016)
This doctoral thesis contains three essays on the macroeconomic impact of inflation targeting: (1) Inflation-targeting regime, as a framework for monetary policy conduct, has been adopted by central banks in thirty countries. Some of these countries enjoy high incomes while others have middle incomes. In contrast to the development-based classification –often applied in the literature, thus ignoring income disparity– this study employs income-based classification in constructing the data sample. The objective is to investigate, using a panel of middle-income countries, whether inflation targeting is a good remedy for high inflation. In addition to the commonly used covariates in the literature, this study also includes in its covariate matrix the worldwide governance indicators as proxy for institutional quality. The findings exhibit a significant reduction of inflation and its volatility among the inflation-targeting adopters compared to the non-adopting middle-income countries. The results are robust to the exclusion of high inflation episodes, and to using the alternative measures of inflation. The results are also robust to the post-estimation sensitivity tests recommended for such empirical analysis. (2) Many economists acknowledge the paramount role that foreign investment plays in fostering economic development and growth via integrating economies around the globe. Studies have shown that foreign investment, particularly foreign direct investment (FDI) is attracted to countries that exhibit good governance, low uncertainty and a high degree of macroeconomic stability. The literature also argues that monetary policy under inflation targeting (IT) mitigates uncertainty, enhances governance and brings macroeconomic stability to the adopting countries. Hence, it would seem that the IT-adoption should enable the adopting countries attract the largest FDI inflows. To verify this conjecture, this study performs a comparison between the IT-adopting countries and the non-adopters in attracting FDI. Using a panel of OECD and middle-income countries, the empirical findings exhibit an interesting but contradicting pattern: when it comes to the OECD countries, the results show that the IT-adopters do better than the non-adopters in attracting the FDI inflows. For the middle-income countries, however, the IT-adoption appears to have the opposite effect: a significant reduction in the FDI inflows is witnessed among the IT-adopters compared to their counterparts. The results are robust to the post-estimation sensitivity tests. (3) Inflation targeting, as a monetary-policy framework, is said to promote economic efficiency and growth. Yet, when evaluating the macroeconomic performance of inflation-targeting regimes, the existing literature only emphasizes the dynamics of inflation and the costs associated with taming inflation. There is hardly any assessment of the claim of efficiency and growth. To fill this gap, and to measure the causal impact of inflation-targeting adoption on economic efficiency, we compare the dynamics of output growth and long-term unemployment between countries that have adopted inflation targeting and the non-adopting countries. Our findings seem to refute the efficiency claim, and paint a bleak picture of inflation targeting: when compared to the countries that did not adopt inflation targeting, there is a significant reduction in the average growth rate among the inflation-targeting adopters by over ½ percentage point. Additionally, long-term unemployment significantly rises among the inflation-targeting countries by almost 2 percentage points as compared to the non-adopters. These results are robust to both the exclusion of the outlier observations and to the sensitivity tests recommended for such analysis.
Keywords: Inflation Targeting; Governance Institutions; FDI; Growth; Unemployment; Sacrifice Ratios